Посольство до папи Сикста ІV з посланням Мисаїла у світлі деяких документів Ватиканського таємного архіву - Заторський, Н. (Міжнародні зв’язки України: наукові пошуки і знахідки, 2017)
У статті проаналізовано всі відомі на сьогодні згадки та докази на
користь того, що посольство до папи Сикста IV з посланням Мисаїла
відбулося, та доведено їхню непереконливість або й хибність. Автор
відслідковує джерела, на підставі яких постали хибні тлумачення, та
шляхи їх розповсюдження в українській, польській та частково російській історіографіях. The article considers the Epistle of Misael to the Pope Sixtus IV of 1476,
which was first published by the Uniate metropolitan Hypatius Potij in 1605.
Though its authenticity was definitely proved only at the end of 20th century,
the fate of this letter, particularly with regard to the envoys who allegedly
brought the charter to Pope Sixtus IV, has been discussed from the moment of
its first edition until today. However, no special research was made concerning
existing theories about this embassy. The article aims to fill this gap. A particular
attention is paid to the thesis of the first publisher of the charter, who
considered the noble Ruthenian Ivan Soltan and the Chancellor of the Great
Duchy of Lithuania Jakub as the envoys with the Epistle of Misael.
The author demonstrates that the title of the document, which appeared in
the first edition of 1605, had been lacking in the original manuscript (now lost)
and was invented by metropolitan Hypatius Potij. He presents the ways by
which Potij’s thesis about two envoys to Pope Sixtus IV was spread in the
Ukrainian and Polish historiography of the 17th through 19th centuries. The
author also examines another source about two envoys with Misael’s charter
to Pope Sixtus IV — Elucidarius errorum ritus ruthenici by Jan Sacran, edited
at the beginning of the 16th century, to which Mykhailo Hrushevsky and other
scholars referred, and shows that this document was a source of misrepresentation,
wherefrom the idea of two envoys with the Epistle of Misael to
Pope Sixtus VI derived. Based on a false quotation of Elucidarius, this idea is
still circulating in the contemporary Ukrainian historiography. Therefore, this
article is to correct these fallacious ideas of the embassy with Misael’s charter
to Pope Sixtus IV. In addition, the author identifies one of the written sources,
to which Jan Sacran referred in his treatise. He also traces back some 20th
century erroneous ideas of the authorship of the Epistle of Misael that partially
exist in the Ukrainian historiography even today. Finally, the article is
supplemented by a report from Codex Arm. XXXII 21 from the Vatican Secret
Archives that sheds light on the personality of Alexander Soltan, one of the
alleged envoys with Misael’s charter. The author analyzes the content of the
Codex Arm. XXXII 21 and argues the significance of this document in the
solution of the question whether the embassy to Pope Sixtus IV has ever taken place.